Quantitative trait loci for root architecture traits correlated with phosphorus acquisition in common bean - Beebe, Stephen E.; Rojas, M.; Yan, X; Blair, Matthew W.; Pedraza García, Fabio; Muñoz Arboleda, Fernando; Tohme, Joseph M.; Lynch, Jonathan P. (Wiley, 2006)
Low soil P availability is a primary constraint to common bean (Phaseolus vulgaris L.) production in Latin America and Africa. Substantial genotypic variation in bean adaptation to low phosphorus (LP) availability has been linked with root traits that enhance the efficiency of soil foraging. The objectives of this study were to identify quantitative trait loci (QTLs) for P accumulation and associated root architectural traits, to facilitate genetic improvement and to reveal physiological relationships. Eighty-six F5.7 recombinant inbred lines (RILs) were developed from a cross between G19833, an Andean landrace with high total P accumulation, and DOR 364, a Mesoamerican cultivar with low total P accumulation in LP conditions. A genetic map constructed with restriction fragment length polymorphisms (RFLPs), microsatellites, and PCR-based markers covering 1703 centimorgans (cM) total genetic distance and all eleven linkage groups (LGs) was used for QTL analysis. Seventy-one RILs were evaluated in the field at high phosphorus (HP) and LP for P accumulation, total root length (RL), specific RL, and plant dry weight (DW), while all 86 RILs were evaluated in a hydroponic system in the greenhouse for tap, basal, total, and specific RL and plant DW. Phosphorus accumulation in the field correlated with root parameters measured in the greenhouse. A total of 26 individual QTLs were identified for P accumulation and associated root characters using composite interval mapping (CIM) analysis. Phosphorus accumulation QTLs often coincided with those for basal root development, thus, basal roots appear to be important in P acquisition. Independent QTLs were identified for basal and taproot development, and for specific RL. Distinct QTLs for greater specific RL had positive, null and negative effects on P accumulation. Our results confirm the importance of root structure for LP adaptation and highlight the need for a more detailed understanding of root architectural traits for phenotypic as well as marker-aided selection of more P-efficient crops.